Conservation of the sequence of islet amyloid polypeptide in five mammals is consistent with its putative role as an islet hormone. - Nishi, M (1989)
Islet amyloid polypeptide (IAPP) is a 37-amino acid peptide found in the pancreatic amyloid deposits of type II (non-insulin-dependent) diabetic patients and insulinomas. We previously reported the nucleotide sequence of a human cDNA, which indicated that IAPP is a C-terminally amidated peptide derived by proteolytic processing of an 89-amino acid precursor. We now report the isolation of cDNA clones coding for cat, rat, mouse, and guinea pig IAPP precursors, obtained using the combination of "amplification of homologous DNA fragments" (AHF) and "rapid amplification of cDNA ends" (RACE). The predicted structure of IAPP precursors from these four mammals revealed that the IAPP moiety of each is derived from an 89- to 93-amino acid precursor by proteolytic processing and is likely to be amidated at the C terminus. The predicted amino acid sequence identities between the IAPP domains of these four mammals and human IAPP were 89% (cat), 84% (rat and mouse), and 78% (guinea pig). Within the IAPP domains, the N-terminal and C-terminal amino acid sequences are very highly conserved among the mammals, as is also the case with a structurally related neuropeptide, calcitonin-gene-related peptide (CGRP), suggesting that IAPP and CGRP interact with similar though not identical receptors. By contrast, the N- and C-terminal propeptides of the IAPP precursor show very little sequence conservation, which suggests that these regions do not represent additional biologically active molecules. Interspecies variations in the amino acid sequence of residues 20-29 of IAPP may account for the presence of amyloid deposits in the islets of humans and cats and their absence in rats and mice.